Frequency of serrated polyposis syndrome recognition by community endoscopists - McWhinney, Connor D.; Lahr, Rachel E.; Rex, Douglas K. (Endoscopy International Open, 2023)
Background and study aims Some data indicate serrated polyposis syndrome (SPS) is underdiagnosed. We determined the frequency of SPS diagnosis by community endoscopists prior to referral to a tertiary center.Patients and methods We performed a retrospective analysis of a prospectively collected database of SPS patients at a tertiary academic hospital. There were 212 patients who were referred to our center for resection of one or more lesions detected at a prior colonoscopy and who had records available that allowed determination of whether SPS was diagnosed before referral.Results Only 25 of 212 patients (11.8%) had a diagnosis or suspicion of a polyposis syndrome prior to referral, and only 12 patients (5.7%) had a specific SPS diagnosis made prior to referral. Among 187 patients diagnosed at our center, 39 had sufficient serrated lesions removed and documented in outside records to meet SPS criteria prior to referral, but the diagnosis was not made by the referring physician despite adequate numbers of lesions resected. The remaining cases required lesions removed at our center to meet SPS diagnostic criteria. Limitations were a single center, single expert endoscopist.Conclusions SPS is the most common colorectal polyposis syndrome, but it remains underdiagnosed by community endoscopists. Underdiagnosis may contribute to post-colonoscopy colorectal cancer in patients with SPS.
Keywords: Polyps / adenomas / ...; Endoscopy Lower GI Tract; colonoscopy; sessile serrated lesion; serrated polyposis syndrome